Amino induced high-loading atomically dispersed Co sites on N-doped hollow carbon for efficient CO2 transformation. Issue 46 (18th May 2022) - Yun, Ruirui; Li, Tuanhui; Zhang, Beibei; He, Lei; Liu, Shoujie; Yu, Can; Chen, Zheng; Luo, Shizhong
Abstract : A high-loading atomically dispersed Co site catalyst has been constructed by a modified N-coordination-assisted strategy. Abstract : Herein, a novel strategy has been proposed to design a hollow structure via post-modified N sites coordinating to metal species. As a result, an atomically dispersed Co site catalyst with high loading has been obtained and has shown superb performance in CO2 cycloaddition to ethylene carbonate. This novel avenue can be extended to other atomically dispersed metal catalysts with high loading.